Integration of Education for Sustainable Development into Interactive Multimedia to Enhance Students’ Environmental Awareness in Chemistry Learning - Najikhatul Umniyah; Sisca Rahmadonna (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study was motivated by the limited integration of Education for Sustainable Development (ESD) values in chemistry learning, particularly in acid-base topics, and the need for learning media capable of connecting chemistry concepts with environmental issues contextually. The study aimed to develop ESD and Chemo-Entrepreneurship (CEP)-based interactive multimedia, analyze its feasibility and practicality, and examine its effectiveness in improving students’ environmental awareness in chemistry learning. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed multimedia integrated acid-base concepts with sustainability issues such as acid rain, water pollution, household chemical usage, environmentally friendly products, interactive quizzes, feedback, and CEP-based project activities. Data were collected through expert validation sheets, teacher and student response questionnaires, and environmental awareness questionnaires administered to experimental and control classes. Data were analyzed using descriptive statistics and independent samples t-tests. The findings revealed that the multimedia was categorized as highly feasible and highly practical, with media validation scores improving from 73% to 83% after revision, while material validation reached 89%. Student and teacher responses reached 89% and 92%, respectively. The posttest results showed a significant difference between the experimental and control groups (p = 0.014), indicating that the ESD-CEP-based interactive multimedia was effective in improving students’ environmental awareness in chemistry learning.